PENERAPAN MODEL PEMBELAJARAN PBL UNTUK MENGANALISIS KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS DITINJAU DARI MINAT BELAJAR PESERTA DIDIK PADA MATERI DERET ARITMATIKA - Cahyani, Rianti; Marwan, Silmi Aulia; Kosasih, Usep (Universitas Islam Nusantara, 2025)
Abstract There are still problems in learning mathematics, many students consider learning mathematics as a difficult lesson, especially because of the lack of interest in learning mathematics. One of the reasons is the low ability to understand mathematical concepts and students' interest in learning. To overcome this, the researcher applies a problem-based learning model, namely Problem-Based Learning (PBL) in the hope of increasing students' interest and understanding of concepts. The purpose of this study is to measure the ability to understand mathematical concepts and learning interests of participants and analyze the ability to understand mathematical concepts reviewed from their learning interests through arithmetic series material. The study uses a quantitative method with a One-Shot Case Study design, which involves one class (30 people) as the research subject. The research instrument consisted of a description test to measure understanding of mathematical concepts and a questionnaire to measure learning interest. The results of the study showed that students' ability to understand mathematical concepts exceeded the KKTP with an average score of 87.83. 60% of students' learning interest was classified as moderate learning interest, and the results of the ability to understand mathematical concepts with